2022
DOI: 10.1016/j.devcel.2021.12.023
|View full text |Cite
|
Sign up to set email alerts
|

An ex vivo system to study cellular dynamics underlying mouse peri-implantation development

Abstract: Summary Upon implantation, mammalian embryos undergo major morphogenesis and key developmental processes such as body axis specification and gastrulation. However, limited accessibility obscures the study of these crucial processes. Here, we develop an ex vivo Matrigel-collagen-based culture to recapitulate mouse development from E4.5 to E6.0. Our system not only recapitulates embryonic growth, axis initiation, and overall 3D architecture in 49% of the cases, but its compatibi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 68 publications
0
43
0
1
Order By: Relevance
“…Notably, the postulated tension release at the embryo-substrate interface exactly corresponds to the condition required for pTE cells to constrict apically, invaginate and form ExE -which had been achieved ex vivo only by removing the mTE and releasing tension acting on the pTE (Bedzhov et al, 2014;Ichikawa et al, 2022). Light-sheet microscopy and measurement of the pTE cell aspect ratio showed that pTE cells indeed undergo apical constriction (Figure 4F-G) within the predicted time interval (Figure 4E), indicating that the 3E-uterus recapitulates the embryo-uterus interaction, releasing the TE tension and enabling the development of the whole embryo ex vivo for the first time.…”
Section: A Droplet-wetting Process Can Explain Embryo-uterus Tissue-t...mentioning
confidence: 96%
See 3 more Smart Citations
“…Notably, the postulated tension release at the embryo-substrate interface exactly corresponds to the condition required for pTE cells to constrict apically, invaginate and form ExE -which had been achieved ex vivo only by removing the mTE and releasing tension acting on the pTE (Bedzhov et al, 2014;Ichikawa et al, 2022). Light-sheet microscopy and measurement of the pTE cell aspect ratio showed that pTE cells indeed undergo apical constriction (Figure 4F-G) within the predicted time interval (Figure 4E), indicating that the 3E-uterus recapitulates the embryo-uterus interaction, releasing the TE tension and enabling the development of the whole embryo ex vivo for the first time.…”
Section: A Droplet-wetting Process Can Explain Embryo-uterus Tissue-t...mentioning
confidence: 96%
“…Cell counts for E4.5-E6.0 in utero embryos were obtained from the previous study (Ichikawa et al, 2022).…”
Section: Embryo Staging By Cell Numbersmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, many groups demonstrated the recapitulation of the implantation-like signal and postimplantation development of mammalian blastocysts upon the gastrulation stage using biocompatible gels and optimized culture methods [ 54 , 55 , 56 , 57 , 58 , 59 ], although the development of the embryos in these studies was limited upon the gastrulation and three-germ-layer segregation, which was far from the hindlimb formation stage (E11 in mice) as reported in the ex utero mouse study [ 52 ]. Thus, in vitro reconstitution of the uterus (“uteroid”, named as PSC-derived uterus-like organoid) from PSCs would make it feasible to achieve omnis ex vivo full-term embryonic development only using stem cells.…”
Section: Female Reproductive Organs Required For Full-term Developmen...mentioning
confidence: 99%